Successful Treatment of Early Relapsed High-Risk AML After Allogeneic Hematopoietic Stem Cell Transplantation With Biomodulatory Therapy - Kattner, Anna-Sophia; Holler, Ernst; Herr, Wolfgang; Reichle, Albrecht; Wolff, Daniel; Heudobler, Daniel (Frontiers in Oncology, 2020)
Early relapse of acute myeloid leukemia (AML) after allogeneic hematopoietic stem cell transplantation (allo-HSCT) is an often unsuccessful therapeutic challenge. Since treatment options are few and efficacy is low, new approaches such as de novo allo-HSCT, targeted therapies and biomodulatory drugs have been developed, albeit prognosis is very poor. In this manuscript we present an unusual case of a patient with high-risk AML with an unbalanced jumping translocation and FLT3-TKD (low) mutation who presented with early relapse (FLT3 negative) after allo-HSCT, refractory to one cycle of azacytidine and discontinuation of immunosuppression (IS). As salvage therapy, the patient received a biomodulatory therapy consisting of low-dose azacytidine 75 mg/day (given s.c. d1–7 of 28), pioglitazone 45 mg/day orally, and all-trans-retinoic acid (ATRA) 45 mg/m2/day orally achieving a complete remission after two cycles of therapy. Even after cessation of treatment after 5 cycles, the patient remained in complete remission with full chimerism in peripheral blood and bone marrow for another 7 months. In conclusion, we report about an unusual case of long-lasting complete remission of early relapsed high-risk AML after allo-HSCT treated with azacytidine, pioglitazone and ATRA after standard of care treatment with HMA and discontinuation of IS failed.